Effect of the type of maternal pushing during the second stage of labour on obstetric and neonatal outcome: a multicentre randomised trial—the EOLE study protocol. Issue 12 (20th December 2016) - Barasinski, Chloé; Vendittelli, Françoise
Abstract : Introduction: The scientific data currently available do not allow any definitive conclusion to be reached about what type of pushing should be recommended to women during the second stage of labour. The objective of this trial is to assess and compare the effectiveness of directed open-glottis pushing versus directed closed-glottis pushing. Secondary objectives are to assess, according to the type of pushing: immediate maternal and neonatal morbidity, intermediate-term maternal pelvic floor morbidity, uncomplicated birth, and women's satisfaction at 4 weeks post partum. Methods and analysis: This multicentre randomised clinical trial compares directed closed-glottis pushing (Valsalva) versus directed open-glottis pushing during the second stage of labour in 4 hospitals of France. The study population includes pregnant women who received instruction in both types of pushing, have no previous caesarean delivery, are at term and have a vaginal delivery planned. Randomisation takes place during labour once cervical dilation ≥7 cm. The principal end point is assessed by a composite criterion: spontaneous delivery without perineal lesion (no episiotomy or spontaneous second-degree, third-degree or fourth-degree lacerations). We will need to recruit 125 women per group. The primary analysis will be by intention-to-treat analysis, with the principal results reported as crude relative risks (RRs) with their 95% CIs. A multivariate analysis will be performed to take prognostic and confounding factors into account to obtain adjusted RRs. Ethics and dissemination: This study was approved by a French Institutional Review Board (Comité de Protection des Personnes Sud Est 6:N°AU1168). Results will be reported in peer-reviewed journals and at scientific meetings. This study will make it possible to assess the effectiveness of 2 types of directed pushing used in French practice and to assess their potential maternal, fetal and neonatal effects. Findings from the study will be useful for counselling pregnant women before and during labour. Trial registration number: Agence national de sécurité du médicament et des produits de santé (ANSM): 150099B-22 and IDRCB: 2014-A01920-47. ClinicalTrials.gov: NCT02474745 . Pre-result stage.